Household food insecurity in Malaysia: findings from Malaysian Adults Nutrition Survey - Selamat, Rusidah; Ahmad, Hasnan; Chong, Zhuo Lin; Zainuddin, Ahmad Ali; Mohd Shariff, Zalilah; Mohd Abu Bakar, Wan Azdie (Malaysian Medical Association, 2015)
Introduction: Food security is an essential universal dimension of household well-being. Food security is usually defined as an access by all people at all times to enough food for an active and healthy life. The deprivation of basic need represented by food insecurity is undesirable.